Economics of enterprise : course book for practical classes and independent work of students. - Shevchenko, І.; Dmytriieva, О.; Шевченко, І.; Дмитрієва, O. (FOP Brovin O.V., 2022)
The course book for practical classes and independent work of students “Economics of enterprise” is aimed to provide the theoretical and practical training of bachelors of economic specialties and economic training of bachelors of technical specialties. Each topic of the course book for practical classes and independent work of students “Economics of enterprise” has the following structure: theoretical provisions; recommended videos; theoretical questions; test tasks; individual practical task (tasks); methodical guidelines for solving practical task (tasks); example of solution to practical task (tasks). The course book for practical classes and independent work of students “Economics of enterprise” is intended for students of higher education institutions.
Економіка підприємства : навчальний посібник для практичних занять і самостійної роботи студентів
Keywords: economics of enterprise; basics of functioning of enterprise as an economic entity; formation and using the capital of the enterprise; economic results of the enterprise; enterprise as an economic entity; enterprise management; fixed assets of the enterprise; current assets of the enterprise; personnel of the enterprise and labor productivity; payment of labor of the enterprise's personnel; costs of the enterprise; cost of products; cost of services; cost of works; pricing and financial result of the enterprise; investment activity of the enterprise; 33